Alergi susu sapi - Mulya Safri (Universitas Syiah Kuala, 2008)
Daftar pustaka1. Lifsehitz C, Alergy to cow milk. J.Ped. Neonatal 2005;2:1-7.2. Muraro A, Dreborg S, Halken S et al, Dietary prevention of allergic diseases in infant and small children Part Ill: Critical review of published peer-reviewed observational and interventional studies and final recommendation. Pediatr Allergy Immunol,2004; 15:291-3073. Sampson HA. Adverse reactions to foods.Dalam: Middleton E, Reed CE, Elliot EF, Adkinson NF, Yunginger JW, Busse WW, penyunting. Allergy, Principle and Practice.Edisi ke-4.St.Louis, Mosby,1993:h 1661- 86.4. Host A. Halken S. Approach to feeding problems in the infant and young child. Dalam: Leung DYM, Sampson HA, Geha RS, Szefler SJ, penyunting. Pediatric Allergy principles and practice. Missouri, Mosby, 2003.h.488-94.5. Ebisawa M, Sugizaki C, Ikeda Y, Tachimoto H.Development of food allergy during infancy. APAPARI-KAPARD Joint congress. Seoul, Korea. April 2005.6. Sampson HA.Food allergy. Part I:lmmunopathogenesis and clinical disorders. J.Allergy Clin lmmunol 1999;103:717-287. Burks AW, James JM,Hiegel A,Wilson G, et al.Atopic dermatitis and food hypersensitivity reactions. J Pediatr 1998;132:132-68. Sicherer Sh,Sampson HA.Food hypersensitivity and atopic dermatitis: Pathofysiology, epidemiology, diagnosis and management J Allergy Clin lmmunol1999; 104:Sl 14-sl229. Hill DJ, Duke AM, Hosking CS,et al.Clinical manifestations of cow's milk allergy in childhood:II.The diagnosis value of skin tests and RAST. Clin Allergy 1988;18:481-9010. William LW, Bock SL. Skin testing and food challenges for evaluation of food allergy. Immunology and Allergy Clinics of North Amer 1999;19:479-931 L Bishop MJ, Hasting. Naturai history of cow's milk allergy. Clinical outcome. J Pediatr 1990;116:862-7.12. Vanto T, Helpplia S, Juntunen-Backman K, Kalimo K, Klemola T, Korpela R. Prediction of the development of tolerance to milk in children with cow's milk hypersensitivity. J Pediatr 2004;144:218-2213. Eggesbo M, Halvorsen R, Tambs K. Prevalence of parentally perceived adverse reaction to food in young children. Pediatr Allergy lmmunol 1999;10:122-32.14. Host A., Halken S. A prospective study of cow's milk alergy in Danish infants during the first 3 years of life. Alergy 1990;45:587-96.15. Hest A. Cow's milk protein alergy and intolerance in infancy. Some clinical, epidemiological and immunological aspects. Pediatr Allergy lmmunol1994;5:l-3